Vanguards of longevity: the case of brazilian Air Force military - Vanessa Gabrielle di Lego Goncalves (2017)
In the demographic study of mortality, there has been growing attention to population subgroups that are more likely to rst benet from mortality progress or benet more intensivelythanothers. Some authors dene these subgroups as vanguard populations (Evgueni et al. 2014; Caselli and Luy 2014). Focusing on mortality trajectories of vanguard populations can be instrumental to disentangling the pathways to longer lives and isolating specic risk factors (Evgueni et al. 2014; Caselli and Luy 2014). Hence, we use a novel longitudinal military dataset for Brazilian Air Force personnel (BAF), considering them as a vanguard population subgroup in Brazil to explore two main questions: 1. Given a highly selected (vanguard) population subgroup in a developing country, what is the degree of survival selection among its members and what are the factors associated to it? 2. Are there other possible candidates as vanguard groups in Brazil? What is the true advantage of the military compared to other low mortality subgroups? Oursampleiscomposedof N =13,341individuals,comprisedof D =3,084 deaths (23.11% of total sample) and S =10,257 survivors. We employ non-parametric (KM curves) and semi-parametric (Cox regression) approaches to address question number 1, and compute probabilities of death by single ages derived from the incidence rates to compare with other vanguard population groups in Brazil and address question number 2. We show that even in a selected setting place of birth and educational background are still important to explain mortality dierenetials, suggesting scarring eect among the BAF personnel